Kidney histopathology of white rats (Rattus norvegicus) fed a high-fat diet, curcumin supplement, and turmeric powder (Curcuma longa) - Tyas Rini Saraswati; Nur Exmah; Silvana Tana (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.